Crystallization and Structural Characterization of Dimeric and Trimeric Forms of (Neocuproine)CdFe(CO)4. (11th March 2014) - Kolb, Torsten; Arif, Atta M.; Ernst, Richard D.
Abstract : The previously reported (neocuproine)CdFe(CO)4 has been found to crystallize as either a dimer or a trimer depending on the procedure used. These species exist as nearly planar four- and six-membered rings composed of alternating cadmium and iron atoms. The trimeric form is reasonably similar to its 2, 2′-bipyridyl analogue, while the dimeric form had not been observed previously for aL x CdFe(CO)4 complex. The space group for the dimeric isomer is C 2/ c, witha = 20.7044 (3), b = 12.2169 (2), c = 13.7837 (2)  Å, andβ = 98.1226 (11)°, while for the trimeric isomer the space group is P 1 ̅, witha = 14.5056 (1), b = 15.4331 (1), c = 17.3372 (2)  Å, α = 110.0059 (3)°, β = 104.2580 (4)°, andγ = 95.2796 (5)°.